Distribution of microbes and antimicrobial susceptibility in patients with diabetic foot infections in South China - Liu, Wei; Song, Liying; Sun, Wei; Fang, Weijin; Wang, Chunjiang (Frontiers in Endocrinology, 2023)
Background To investigate the distribution of microbes and drug susceptibility in patients with diabetic foot infections (DFI) and provide guidance for clinical empirical treatment and the rational selection of antibacterial drugs. Methods Retrospective analysis of the pathogenic bacterium distribution and antimicrobial susceptibility isolated from 581 DFI patients with different Wagner grades. Results The 534 positive samples included 473 cases (88.58%)) of monomicrobial infections and 61 cases (11.42%) of polymicrobial infections before antibiotic therapy. A total of 656 strains were cultivated, including 387 (58.99%) strains of gram-positive organisms (GPOs), 235 (35.82%) gram-negative bacilli (GNB), and 21 (3.20%) fungal strains. Polymicrobial infections mainly occurred in patients with Wagner grade 3-4 ulcers. GPOs were predominant in Wagner grades 1-3 (grade 1: 96.67%, grade 2: 76.52%, grade 3 62.81%), and the most common was Staphylococcus aureus (grade 1: 31.66%, grade 2: 33.04%, grade 3 35.53%). GNB were predominant in grades 4-5 (grade 4: 51.46%, grade 5:60%), and the most common GNB in Wagner grades 4-5 was Proteus (grade 4:27.88%, grade 5: 42.86%), while the most common GPO was Enterococcus (grade 4:34.48%, grade 5:25.00%). Staphylococcus (including MRSA) and Enterococcus were still highly sensitive to vancomycin, linezolid, and tigecycline. Most GNB were still highly sensitive to meropenem, tigecycline, ertapenem, and amikacin. Proteus was most sensitive to amikacin (97.14%), followed by meropenem (92%) and ertapenem (80%). Conclusion The distribution of microbes and antimicrobial susceptibility in DFI patients varied with different Wagner grades. The most appropriate antimicrobial therapy should be selected based on the pathogen culture and antimicrobial susceptibility.